Alienasi Digital di Indonesia: Analisis Pemikiran Karl Marx dan Dampak Sosial Media Terhadap Alienasi Manusia - H, Hariyanto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Social media, as an influential platform in human social life, often leads to alienation, where individuals become distorted from their surrounding reality. This research falls under literature study or library research, utilizing content analysis to explore alienation arising from interactions with social media, with a specific focus on the Indonesian context. Karl Marx's Alienation Theory is used as a foundation to comprehend this phenomenon. Through content analysis, the research identifies patterns of behavior and messages on social media contributing to individual alienation. The study's findings are expected to provide further insights into the impact of social media on the essence of humanity, particularly within the context of alienation in Indonesian society.